PENGARUH LAGU “OKE GAS” SEBAGAI STRATEGI KOMUNIKASI POLITIK BERBASIS POP CULTURE TERHADAP ELEKTABILITAS PASANGAN PRABOWO-GIBRAN PADA PEMILU 2024 DI KECAMATAN TEMBALANG - Ari Sigit; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
The development of digital media has driven a transformation in political communication toward a more interactive approach closely tied to popular culture. In the 2024 Indonesian General Election, the Prabowo Subianto and Gibran Rakabuming Raka campaign leveraged the